First record of Smilodon Lund (Felidae, Machairodontinae) in Tierra del Fuego island (Chile) - Prevosti, Francisco Juan (2013)
In this contribution we describe the first record of Smilodon for Tierra del Fuego Island, and discuss its relevance.